Investigative journalism : context and practice - Burgh, Hugo de, 1949-; Bradshaw, Paul (Data journalist) (London ; New York : Routledge, 2021)
Investigative Journalism: Context and Practice explores the history, theory and practice of investigative journalism around the world. Starting with a history of investigative journalism and examining key events such as Watergate in the U.S. and the thalidomide scandal in the U.K., Hugo de Burgh and his colleagues explain how investigative journalism should be understood within the framework of the mass media, how it relates to the legal systems in the U.S., the U.K. and the European Union, the place of ethics in investigative journalism, and the influence of new technologies and the Internet on journalistic practices.
PART 1 Context -- 1 Introduction: a higher kind of loyalty? -- 2 The emergence of investigative journalism -- 3 Thirty years of British investigative journalism -- 4 Some issues surrounding investigative journalism -- 5 Critical approaches to the media: the changing context for investigative journalism: -- 6 Globalising media agendas: the production of journalism -- 7 The English legal framework for investigative journalism -- 8 The regulatory and ethical framework for investigative journalism -- 9 Journalism and new technology -- PART 2 Practice -- 10 Investigating corporate corruption: an example from BBC's File on Four -- 11 Local power and public accountability: an example from the East Midlands -- 12 Scrutinising social policy: an example from Channel 4's Dispatches -- 13 Exposing miscarriages of justice: an example from BBC's Rough Justice -- 14 Gravedigging: the case of 'the Cossacks' -- 15 Pillaging the environmentalists: an example from The Cook Report -- 16 High politics and low behaviour: the Sunday Times Insight -- 17 Interfering with foreigners: an example from First Tuesday.
OCLC-licensed vendor bibliographic record.
Keywords: Investigative reporting; Journalism; LANGUAGE ARTS & DISCIPLINES / Journalism; SOCIAL SCIENCE / Media Studies